Subject Verb Agreement Test Outcome Analysis - Rifiyanti, Hafizah; Hardianti, Hardianti; Nggolaon, Desriani (BABASAL English Education Journal, 2023)
This study aims to evaluate the effectiveness of the practice method given to students in the context of subject-verb agreement. The research method used is the descriptive qualitative method, which leads to an in-depth analysis of the common error patterns of the students, as well as to observe the development of students' understanding over time. The results of this study show that the subject-verb agreement learning method has a positive impact on students' understanding and enables them to master this concept well. The implication of this study is the importance of using effective learning methods in overcoming subject and verb agreement errors, which are important aspects of English grammar. With the right approach, students can improve their understanding of subject and verb rules in English, thus improving their overall language skills.